Dynamical and musculoskeletal effects of arm prosthesis on sprint running for runners with unilateral transradial deficiency - Motomu NAKASHIMA; Mashio KUBOTA (Mechanical Engineering Journal, 2022)
In sprint races for runners with upper limb amputation/deficiency, it is allowed to use arm prostheses. However, there are few studies about arm prostheses for sprint running and about runners with upper limb amputation/deficiency. The objective of this study was to investigate the dynamical and musculoskeletal effects of arm swing and prosthesis on sprint running for runners with unilateral transradial deficiency. For this objective, the arm swing of runners with unilateral transradial deficiency was measured, and analyzed by using inverse dynamics calculation and musculoskeletal simulation. As the result of inverse dynamics analysis, it was found that the arm swing had the effect to increase the vertical ground reaction force, and that attaching prosthesis enlarged that effect. With respect to the anteroposterior and lateral directions, it was suggested that the arm swing contributed to maintaining balance and that the prosthesis helped to produce the force which counteracted the force produced by the intact limb. As the result of musculoskeletal analysis, it was found that the impulses of the muscle forces for the deficient limb were basically smaller than those for the intact limb. However, the ratios for the particular muscles were very large. With respect to the effect of attaching prostheses, it was found that most of the muscle force impulses increased by attaching the prostheses. In particular, the ratios of brachioradialis were significantly larger than the other muscles.